The Wildfowl Trust expedition to Spitsbergen, 1973 - Jackson, E E; Ogilvie, M A; Owen, M (Wildfowl, 1974)
An expedition to Spitsbergen in summer 1973 to study and ring Barnacle Geese Branta leucopsis is described. 416 geese were ringed, and weights and measurements taken. Other studies involved food and feeding behaviour of the geese, general botanical recording and filming. 94% of the 350 geese marked with large lettered plastic rings have been identified back on the wintering grounds in Scotland.